1991
DOI: 10.1007/bf00216964
|View full text |Cite
|
Sign up to set email alerts
|

On the sufficiency of the velocity field for perception of heading

Abstract: All models of self-motion from optical flow assume the instantaneous velocity field as input. We tested this assumption for human observers using random-dot displays that simulated translational and circular paths of movement by manipulating the lifetime and displacement of individual dots. For translational movement, observers were equally accurate in judging direction of heading from a "velocity field" with a two-frame dot life and a "direction field" in which the magnitudes of displacement were randomized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
107
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 33 publications
9
107
1
Order By: Relevance
“…However, Warren et al (1991; found no decline in performance with full-screen displays in which the directions of individual vectors were randomized within a 45°envelope. This indicates that the redundancy in the global flow field allows the visual system to achieve high precision despite such local errors.…”
Section: Postural Adjustmentsmentioning
confidence: 77%
“…However, Warren et al (1991; found no decline in performance with full-screen displays in which the directions of individual vectors were randomized within a 45°envelope. This indicates that the redundancy in the global flow field allows the visual system to achieve high precision despite such local errors.…”
Section: Postural Adjustmentsmentioning
confidence: 77%
“…Crowell et al 1998). Otherwise, the direction of locomotion is assumed to be primarily inferred from the characteristic optic¯ow induced on the eyes during locomotion (Warren and Hannon 1990;Warren et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of independently moving objects in the optic flow field has been shown to impair heading judgment only when the object moves across the direction of travel, obscuring the veridical focus of expansion (Warren & Saunders, 1995;Royden & Hildreth, 1996). Subjects can also tolerate significant amounts of velocity noise in the optic flow display, suggesting that heading perception primarily relies on the directional pattern of motion in the optic flow field (Warren, Blackwell, Kurtz, Hatsopoulos, & Kalish, 1991).…”
Section: Introductionmentioning
confidence: 99%